If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3g + -11 = 6 + 12(g + 4) Reorder the terms: -11 + 3g = 6 + 12(g + 4) Reorder the terms: -11 + 3g = 6 + 12(4 + g) -11 + 3g = 6 + (4 * 12 + g * 12) -11 + 3g = 6 + (48 + 12g) Combine like terms: 6 + 48 = 54 -11 + 3g = 54 + 12g Solving -11 + 3g = 54 + 12g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-12g' to each side of the equation. -11 + 3g + -12g = 54 + 12g + -12g Combine like terms: 3g + -12g = -9g -11 + -9g = 54 + 12g + -12g Combine like terms: 12g + -12g = 0 -11 + -9g = 54 + 0 -11 + -9g = 54 Add '11' to each side of the equation. -11 + 11 + -9g = 54 + 11 Combine like terms: -11 + 11 = 0 0 + -9g = 54 + 11 -9g = 54 + 11 Combine like terms: 54 + 11 = 65 -9g = 65 Divide each side by '-9'. g = -7.222222222 Simplifying g = -7.222222222
| 50+5x=200+2x | | 3x-(-2x)= | | 2m-1=6+11(m+1) | | y=4(+5)-8 | | y=4(5)-8 | | y=4(4)-8 | | 3=-1+8x | | 6y-5x=0 | | 6x^2+7=0 | | 18-4y=-2(6+2y) | | y=4(-1)-8 | | 2y^2-2y+37=y^2+16 | | 6t+5(1-3t)= | | 2x^2-5x+2=(x-3)(x-2)+3x | | 4x+1=2x-17 | | -3+4m=2-3m | | N-12=50n+94 | | 2y=3x-8 | | -5x-6x=0 | | U=7(4n+35)+8(n+1) | | a+5=-5a-13 | | x-2.1=2.4 | | 15-x=13 | | x-9=-7x-9 | | 12-3(w-7)=15 | | -4y+5y=-4x+2(x-2)+4x+2 | | C=1000+80x | | (5x^2-3x+7)+(2x^2+9x-11)= | | 3x^2+17x+14=0 | | -256=16b | | x+(-17)=-5 | | 0.4k=14 |